A Sustainable Mi Siput Drying Machine Utilizing Solar Panel and IoT - Sunthon, Sharmila; Muhammad Rusydi Muhammad Razif; Mohamad Haiqal Ahmad Zainaddin; Farzana Nazirah Ramlee; Yasak Abdullah (Progress in Engineering Application and Technology, 2025)
Traditional drying methods for mi siput are time-consuming and inefficient, typically necessitating additional oven drying overnight. Many businesses rely on gas-powered furnaces, which pose safety issues owing to potential gas leaks. This project attempts to create a faster, safer drying system that includes wireless monitoring and control, using an ESP32 microcontroller and the Blynk app. The system includes a DHT22 sensor that measures temperature and humidity and sends real-time data to the Blynk application. Users can view changes, receive notifications, and change settings remotely. To provide optimal drying conditions, main elements include a DC fan and incandescent light bulbs. The servo motors function to regulate humidity within a specified range, resulting in effective drying. A rain sensor protects the quality of mi siput by returning the servo motor to its original position and operating the fans during rain. The system is powered by solar energy, which is transmitted via a solar panel to a charge controller and battery. The drying process worked well, with the DHT22 sensor triggering the lights and fans as needed. Notifications from the Blynk app enabled real-time monitoring and control. When the humidity approached 80%, the fans and servo motor continued to function , demonstrating the system's durability. This innovation product improves the drying process for mi siput  by ensuring safety, efficiency, and sustainability. Drying machine that can dry mi siput within 8 hours at a temperature range of 30-40°C.